Prevalence of postpartum depression in a tertiary care centre - Radhakrishnan, Abinaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Postpartum depression (PPD) is characterized as a depressed episode that transpires during pregnancy or within four weeks following childbirth. Diagnosing postpartum depression is essential, since it can hinder normal maternal-infant attachment and adversely affect both the short-term and long-term development of children. Hence this study was conducted to determine the prevalence of postpartum depression in a tertiary care centre. Methods: A prospective observational study was performed at a tertiary health care center for a period of 6 months. A total of 150 post-natal mothers were included in this study. After getting informed written consent, post-natal mothers were evaluated with the Edinburgh Postnatal Depression Scale (EPDS) at 24-48 hours and at 4 weeks postpartum. The threshold score for identifying severe depression is 13 or higher. All the data’s recorded are entered in Microsoft Excel and analysed using SPSS version 21.0. Results: The study comprised 150 women, of which 24 exhibited postpartum depression. The prevalence of postpartum depression in this study cohort is 16%. It was found that socio-demographic characteristics such as age and occupation together with social variables like pressure to have a male child, and obstetric factors including age at marriage and mode of delivery, were significant predictors of postpartum depression. Conclusions: This study observed a 16% prevalence of postpartum depression among postnatal mothers. With the increasing trend in the prevalence of depression, it is essential to incorporate screening for postpartum depression in all women.